Ultrastructural particularities of the spermatozoon of the cestode Electrotaenia malopteruri (Fritsch, 1886) (Proteocephalidae: Gangesiinae), a parasite of Malapterurus electricus (Siluriformes: Malapteruridae) from the river Nile, Egypt - Brunanská, Magdaléna; Scholz, Tomás; Ibraheem, Mohammed Hassan (Parasitology research, 2004)
The fine structure of the mature spermatozoon of the tapeworm Electrotaenia malopteruri (Fritsch, 1886), a member of a supposedly primitive group of proteocephalidean tapeworms (Proteocephalidae: Gangesiinae), was studied by transmission electron microscopy for the first time. The mature spermatozoon of E. malopteruri is filiform, tapers at both extremities, and contains two axonemes of 9+"1" trepaxonematan type. A helicoidal crested body (60-150 nm thick) is present at the anterior extremity of the gamete. The twisting cortical microtubules (CM) line the periphery of the spermatozoon continuously. The nucleus, a fine cord of moderately condensed chromatin, occupies the middle part (region III) of the spermatozoon. The slightly electron-dense cytoplasm contains electron-dense granules in regions II and III and becomes more electron-dense at the end of region IV. The anterior and posterior extremities of the spermatozoon contain a single axoneme. Two modes of disorganisation of the axoneme at the posterior end of the mature spermatozoa are described for the first time in cestodes. The present data also indicate that the sperm ultrastructure of E. malapteruri shows some characters typical for onchobothriid tetraphyllideans, but it resembles that of Cyclophyllidea in the arrangement of twisting of the CM.
Keywords: Catfishes; nemoci ryb; elektronová mikroskopie; Fresh Water; spermie; Egypt; Spermatozoa; Animals; Male; Microscopy, Electron; Cestode Infections; Fish Diseases; sladká voda; zvířata; mužské pohlaví; sumci; Cestoda; cestodózy